A low temperature solid state reaction to produce hollow MnxFe3-xO4 nanoparticles as anode for lithium-ion batteries. (December 2019) - Yu, Xiaoting; Zhang, Chaoqi; Luo, Zhishan; Zhang, Ting; Liu, Junfeng; Li, Junshan; Zuo, Yong; Biendicho, Jordi Jacas; Llorca, Jordi; Arbiol, Jordi; Morante, Joan Ramón; Cabot, Andreu
Abstract: Hollow Mnx Fe3-x O4 nanoparticles (NPs) with an average size of 15 nm are produced from the solid state reaction of Fe3 O4 –Mn3 O4 heterostructures. These heterostructures are synthesized through the seeded-growth of Mn3 O4 crystal domains on the surface of hollow Fe3 O4 NPs obtained by the nanoscale Kirkendall effect. Fe3 O4 –Mn3 O4 heterostructures are subsequently annealed at 500 °C, enough temperature to promote the interfusion of Fe and Mn ions, but without compromising the hollow geometry. Mnx Fe3-x O4 nanostructures are tested as anode in lithium-ion batteries (LIBs), delivering large lithium storage capacities and high-rate capabilities of 1054 mAh g −1 at 0.1 A g −1 and 369 mAh g −1 at 5 A g −1 . Additionally, hollow Mnx Fe3-x O4 NPs display long cycling stability, with a capacity up to 887 mAh g −1 at 0.3 A g −1 after 450 cycles. The excellent performance of hollow Mnx Fe3-x O4 NPs as anode for LIBs is associated with their crystal structure, composition, and the presence of carbonized ligands, which further promote electrical conductivity and buffer the volume changes during cycling. Additionally, the small particle size and hollow morphology improves the lithium kinetics, structural stability and cycling performance. Graphical abstract: Image 1 Highlights: A new strategy to produce hollow mixed oxide nanoparticles based on the solid state reaction of heterostructures is detailed. Moderate reaction temperatures are able to promote cations interdiffusion without compromising the hollow geometry. NPs produced in this way deliver excellent energy storage capacity, rate capability and cycling stability for LIBs.